Pemanfaatan Media Sosial dan Marketplace Untuk Meningkatkan Daya Saing UMKM Lokal di Kecamatan Girsang Sipangan Bolon - Jamaluddin, Jamaluddin; Harianja, Eva Julia G.; Saragih, Rijois I. E.; Nainggolan, Rena; Purba, Eviyanti N.; Napitupulu, Junika; Manalu, Darwis R.; Hutapea, Marlyna I.; Siringoringo, Rimbun; Perangin-angin, Resianta; Lumbantoruan, Gortap; Simamora, Roni J.; Ijonris, Yusuf (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
This community service activity aims to improve the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Girsang Sipangan Bolon District through the use of social media and marketplace platforms as digital marketing tools. The main challenges faced by local MSMEs include low digital literacy, limited market access, and suboptimal use of technology in product promotion. The program was implemented through initial surveys, training, and workshops for MSME partners. Training materials covered social media management (Instagram and Facebook Business), opening online stores on marketplaces (Shopee and Tokopedia), and promotional content strategies. The results of the program showed a significant improvement in participants' digital skills, such as creating business accounts, regularly uploading content, and managing online stores. Some partners also began to attract new customers outside their local area.